Relationship between training status and stress response in Chinese college student-athletes: chain mediation between sport performance strategies and coping styles - Gao, Jia; Xiang, Jun; Hou, Zhongren; Liu, Hankun (Frontiers in Psychology, 2025)
AimThe stress response is recognized in sport psychology as a complex physiological and psychological reaction elicited by the human body when confronted with challenges or threats. It remains a focal issue in research on athletes’ training status and sport performance.ObjectiveThis study aimed to examine the effects of training status on the stress response of Chinese college student-athletes and to verify the mediating roles of sport performance strategies and coping styles.MethodsA total of 797 Chinese college student-athletes were assessed using the Training Status Scale, Stress Response Scale, Sports Performance Strategy Scale, and Coping Style Scale.Results(1) Significant differences were observed in training status and sport performance strategy across age, gender, and sport level (p < 0.05); significant differences in stress response were found for age and sport level (p < 0.05), but not for gender (p > 0.05); and significant differences in coping styles were found for sport level (p < 0.05), with no significant differences for gender or age (p > 0.05). Male athletes had higher mean scores than female athletes in training status, stress response, and sport performance strategy, while both genders scored similarly in coping style. (2) Training status was significantly negatively correlated with stress response (r = −0.679, p < 0.001), and had a direct negative effect on stress response (β = −0.237, t = −13.539, p < 0.001). Additionally, training status positively predicted sport performance strategy (β = 0.019, t = 10.211, p < 0.001) and coping style (β = 0.131, t = 3.495, p < 0.001); sport performance strategy significantly predicted coping style (β = −0.442, t = −5.879, p < 0.001) and stress response (β = 0.371, t = 29.986, p < 0.001); coping style significantly and positively predicted stress response (β = −0.055, t = −1.435, p < 0.001). (3) Sport performance strategies and coping styles played significant mediating roles between training status and stress response, accounting for 54.33% of the total effect. Specifically, the mediating effect of sport performance strategy was 10.79%, coping style was 32.37%, and the chain mediation of both was 11.18%.ConclusionTraining status is a significant predictor of sport performance strategies, coping styles, and stress responses among college student-athletes. Moreover, sport performance strategies and coping styles mediate the relationship between training status and stress response. These findings are valuable for enhancing training status, stress response, sport performance, and coping styles in collegiate student-athletes, and provide a theoretical foundation for intervention development. However, limitations include the specificity of the sample and reliance on self-reported data. Future research should expand the sample scope and size, and employ multiple assessment methods and instruments to validate these findings.